2018
DOI: 10.1111/php.12999
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Decontamination of Water: Improving the Solar Disinfection Technique (SODIS) with the Use of Nontoxic Vital Dye Methylene Blue

Abstract: Rational use of water is a major challenge for governments and global organizations, with easy and inexpensive interventions being sought by communities that are not supplied with drinking water. In this context, solar disinfection (SODIS) has shown great efficiency for water disinfection. To speed up the process and improve inactivation, we studied the effects of methylene blue (MB) as a photodynamic agent because of its ability to absorb visible light (red wavelength) and generate singlet oxygen as a reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…The most common light sources reported for MB-mediated APDT were lasers (48.5%), LEDs (32%), and lamps (13%). The other light sources category (6.5% in total) includes so-called non-coherent light sources (name taken from publication methodologies), solar radiation, 454–456 optical parametric oscillator (OPO), 457 hand-held photopolymerizer (HHP), 459 endoscopy system, 458 superluminescent diodes (SLED or SLD) 460 and organic light-emitting diodes OLEDs 125,128,129 (Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…The most common light sources reported for MB-mediated APDT were lasers (48.5%), LEDs (32%), and lamps (13%). The other light sources category (6.5% in total) includes so-called non-coherent light sources (name taken from publication methodologies), solar radiation, 454–456 optical parametric oscillator (OPO), 457 hand-held photopolymerizer (HHP), 459 endoscopy system, 458 superluminescent diodes (SLED or SLD) 460 and organic light-emitting diodes OLEDs 125,128,129 (Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…Dyes, such as malachite green, remazole-red (RR), methyl orange, crystal violet and methylene blue (MB) are the most common effluents discharged directly to water resources. MB and RR are being used in several applications including textile and paper industries [1,2]. MB has some medical uses for many therapeutic and diagnostic procedures [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…MB and RR are being used in several applications including textile and paper industries [1,2]. MB has some medical uses for many therapeutic and diagnostic procedures [1][2][3]. However, MB and RR are a carcinogenic, non-degradable materials and causes serious environmental problems against aquatic animals, plants and human beings [4].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of methylene blue were studied by Cardoso‐Rurr et al (2019) as a photodynamic agent to improve the inactivation of the solar disinfection process. The enhanced process is supposed to absorb the red wavelength of the visible light and generate singlet oxygen as reactive species.…”
Section: Drinking Water Disinfectionmentioning
confidence: 99%
“…The enhanced process is supposed to absorb the red wavelength of the visible light and generate singlet oxygen as reactive species. The results indicated that the synergistic extermination effect of the photosensitized methylene blue solar disinfection process inactivated gram‐positive ( Staphylococcus epidermidis or Deinococcus radiodurans ) in addition to the gram‐negative strains ( Escherichia coli or Salmonella typhimurium ) which were spiked in clean mineral water (Cardoso‐Rurr et al, 2019).…”
Section: Drinking Water Disinfectionmentioning
confidence: 99%